(untitled) (Global Journal of Human-Social Science, 2013)
The purpose of this research was to examine the predictive role of attachment styles on loneliness and depression. The sample consisted of 652 (313 females; 339 males) university students. Data were collected by using the relationship scales questionnaire, UCLA-R loneliness scale, and Beck depression inventory. To analyze data, Pearson product-moment correlation analysis and multiple regression analysis was employed. Attachment styles were found to be significantly correlated to loneliness and depression. A significant relationship was also found between loneliness and depression. A significant effect of attachment styles on loneliness and depression was detected.